PENGARUH PEMBERIAN TEPUNG IKAN PAYANGKA TERHADAP KADAR KALSIUM TULANG TIKUS PUTIH - Anasiru, M Anas (Sainstek, 2011)
More less 99% from overall our body calcium resides in in bone and tooth. when does blood calcium degree go down under normal, body take it from bone to fill it again. along with getting old, system balance begins disturbed. Bone loses quicker calcium membanding the ability to fill to return. in general can we say that osteoporosis happen moment bone cells smashing function dominanter membanding bone cells formation function. Osteoporosis well-being problem the insident more will increase along with increase it average age advanced person age. In general this watchfulness aims to detect fish meal gift influence payangka (ophieleotris aporos) (ophieleotris aporos) towards bone calcium degree in white mouse (rattus novergicus strain wistar). This watchfulness kind true experiment designs uses pretest-postest with control group designs, done towards 16 mouses putph (rattus norvegicus galur wistar) as animal tries. sample taking uses complete random plan method. Data that gatherred mouse woof that consist of four groups that is group a shaped woof pars + whole-wheat, group b shaped woof pars + maize flour, group c shaped woof pars + maize flour + fish meal payangka (10 g), and group d shaped woof pars + maize flour + fish meal payangka (20 g); with mouse body heavy development data. to detect to what there fish meal gift influence payangka (ophieleotris aporos) towards white mouse bone calcium degree (rattus norvegicus galur wistar) is used statistics test one way annova, with belief level 99%. Bone calcium degree analysis attributes that found real influence (p